Tuberculosis: through the artist’s eye - Sukumar, Cynthia A. (International Journal of Research in Medical Sciences, 2021)
The history of medicine and art have intersected at several instances over time. Centuries ago, even when many diseases were obscure, art has shed some light over early clinical features and signs of many diseases. This article describes Leonardo Da Vinci’s famous sketch, “The Five Grotesque Heads” and highlights the hints of reference to the age-old infection of tuberculosis. Da vinci’s eye for detail has been known to capture several startling anatomical and pathological features of diseases, which were largely unknown at his time. However, these subtle references give us insight into the clinical presentation of the timeless disease of tuberculosis through the ages.